Peluang Mengembangkan Kebudayaan Desa Berbasis Potensi Desa - Rizki Fatullah (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2020)
Student Work Program Activities Program Has Aims To increase the Potential of Cultural Skills in the Village Community Especially young people. The partners of the activity are non-productive youth in the angsana village, Kec. Mancak. The problem faced is the lack of potential of the agricultural sector so that the culture that will be lifted into superiority angsana village. The method of implementing this service is Survey Through observation, interview and problem analysis. The results of this program are increasing community knowledge and skills regarding the importance of pencak silat culture as a village cultural potential, and increasing public awareness of the importance of Pencak Silat culture.